A critical bicultural pedagogy of dance: Embodying cultural literacy - Darder,Antonia (2018)
The article examines the manner in which the use of a critical bicultural pedagogy of dance within oppressed communities in the United States can support the cultural literacy development of children, their families, and communities. At the heart of this particular examination is the Afro-Puerto Rican practice of Bomba by Grupo Bayano in a Seattle community, where dance praxis serves as a pedagogical means for learning to read the world. As such, a critical bicultural pedagogy of dance functions to support the biculturation process of young children through the use of the body in culturally distinct and transformative ways.